Dental Pain in Cats: A Prospective 6-Month Study. (December 2022) - Palmeira, Isabel; Fonseca, Maria João; Lafont-Lecuelle, Céline; Pageat, Patrick; Cozzi, Alessandro; Asproni, Pietro; Requicha, João Filipe; de Oliveira, Joana
Dental pathology is among the most ubiquitous diseases in cats of all ages. Dental pain is yet to be fully understood in cats and therefore its presence is often missed. To better understand feline dental disease as a pain trigger during routine examination and whether disease severity correlates to the degree of pain, a 6-month prospective study in a cats' only veterinary hospital in Portugal was conducted. Sixty-four cats that randomly presented for different clinical procedures were evaluated. Dental and periodontal abnormalities (primary dental parameters, PDP), as well as clinical signs related to dental pain (secondary dental parameters, SDP), were assessed. All cats underwent an oral cavity examination, upon which, the Feline Acute Pain Scale from Colorado State University Veterinary Teaching Hospital (CPS), was used in order to assess pain. Six PDP (periodontal disease, gingival index, calculus index, tooth resorption, tooth fracture and missing teeth) and five SDP (mouth discomfort, halitosis, hypersalivation, difficulty in holding food and several attempts at prehension of food), were compared with CPS pain scores. All SDP were significantly associated to higher CPS pain scores (p < 0.05). The number of missing teeth was significantly associated to higher CPS pain scores (p < 0.0001). A trend was observed between higher CPS pain scores and tooth resorption (p = 0.08). This study concluded that cats with dental disease feel pain during clinical examination and the pain increases as the severity of the disease progresses.